Women in Engineering Education: Five Strategies to Promote Women in Engineering Education - Nurul Azhani Yunus; Ibham Veza; Ihwan Ghazali (The Indonesian Institute of Science and Technology Research, 2023)
The article explores diverse approaches to advancing women in engineering education, a crucial topic given the pervasive gender imbalance in this domain. The review emphasizes the implementation of educational modifications in the field of engineering with the objective of increasing its attractiveness to female students. These modifications include the incorporation of practical applications and interdisciplinary topics, as well as the utilization of active learning methodologies. The present article suggests the potential of the Maker Movement to promote gender equality in engineering education by highlighting its experiential and innovative pedagogical approach. This study emphasizes the importance of cultivating educational environments that are inclusive and supportive, as they are crucial in advancing gender diversity in engineering education. These learning environments promote participation and facilitate success, especially for female students, by fostering a sense of belonging, addressing unconscious bias, and establishing a hospitable physical setting. Additionally, the significance of introducing engineering concepts at an early stage of K-12 education is presented, arguing that this exposure has the potential to spark the interest of female students, challenge existing stereotypes, and influence their career goals. Finally, this mini review highlights the impact that mentorship can have on encouraging women to pursue careers in engineering. The provision of personalized guidance, assistance in navigating challenges, and demonstration of successful behaviors and attitudes by mentors and role models can greatly enhance the pursuit and persistence of women in engineering careers. In summary, this review article provides strategies for advancing women in engineering education, highlighting the need for a multifaceted approach in order to attain a more diverse and inclusive engineering labor force.